Structural Design and Testing of a Corn Header for Soybean–Corn Intercropping - Zhipeng Cao; Qiqiang Li; Linfeng Chen; Yang Zhou; Junshan Nie; Qi Chen; Yuanfeng Xiao; Shaohao Zhou; Lihua Zhang (Agriculture)
In response to the issues that existing corn headers are not only unsuitable for harvesting under the strip intercropping mode of soybeans and corn but also have the problems of being heavy and causing high harvest losses, a new type of header has been designed. This new header is lighter, reduces harvest losses, and is specifically adapted for use in the strip intercropping mode of soybeans and corn. By analyzing the corn stalks and the growth conditions of the corn, efforts were made to reduce the loss rate of kernels during harvesting, leading to a structural design of the header frame tailored for the strip intercropping mode. Following this, finite element analysis was employed to achieve a lightweight design of the header. The results show that the optimized header is 28.4 kg lighter than the original. The optimal working parameter combination for the combine harvester includes a forward speed of 0.94 m/s, a stalk roll rotational speed of 566.5 r/min, and a kernel moisture content of 25%, under which conditions the grain loss rate of the corn header is 0.32% and the ear loss rate is 1.1%. The development of this specialized corn header is conducive to enhancing both the quality and efficiency of mechanized harvesting in the strip intercropping mode of soybeans and corn.